ANALYSIS AND CONTROL OF FILLING PROCESS DEFECTS USINGSEVEN QUALITY CONTROL TOOLS AT PT ABC - Endang Silaningsih; Isfan Hawari; Tini Kartini (Universitas KH. Abdul Chalim Mojokerto, 2026)
Quality control plays an important role in maintaining product consistency and improving production efficiency. A high level of product defects can lead to material waste, increased production costs, and decreased operational performance. This study aims to identify the dominant types of product defects and analyze the factors causing defects in the production process of cup and lid packaging for the rock Twist product at PT ABC. This research employed a quantitative descriptive method using the Seven Quality Control Tools, including flowchart, Check Sheet, histogram, Pareto diagram, scatter diagram, p-control chart, and cause-and-effect (Fishbone) diagram. The data used in this study were secondary data obtained from production reports and rejected product reports during the 2021 production period. The results indicate that the most dominant defect type is uncentered fill, with a total of 357,326 pieces, followed by overfill (53,672 pieces), underfill (52,481 pieces), and poor coding (3,602 pieces). Based on the Pareto analysis, uncentered fill contributes 76.50% of the total product rejects, making it the primary quality issue in the production process. The scatter diagram analysis shows a positive correlation between the number of cups and lids used in production and the number of rejected products. Furthermore, the p-control chart indicates that the production process is statistically out of control. The cause-and-effect diagram identifies human factors, machine conditions, work methods, and material quality as the primary contributors to product defects. The findings demonstrate that the Seven Quality Control Tools are effective in identifying major sources of quality problems and determining priority areas for process improvement. Improving control in the filling process is expected to significantly reduce product defects and enhance production quality and efficiency.